(untitled) (Journal of Economic Research & Business Administration, 2016)
In present time the venture financing is one of basic factors in development of world economy. This type of financing is effective for development of global economy and development of Kazakhstan. Passing of RK to the innovative economy will decide the problem of low enterprise efficiency, will open new workplaces, will open a road on a reliable collaboration and investments in world economic space. It is a basic source of the new openings. For forming needed: commercial idea, public demand, a businessman is ready to create a venture firm and «risk capital» for financing of venture firm. Today our country stands in the initial stage of development of the venture financing. The article is about current status of the venture financing of innovative projects, problems of development and way of their decision.